Indigenous Knowledge on Health and Use of Herbal Plants as Domestic: A Case Study of Illiterate an Indigenous Caste ‘Bankariya’ - Moktan, Dhana Bahadur (Southwestern Research Journal, 2023)
This study has aim to explore the indigenous knowledge of Bankariyas on health and herbal use practice as domestic cure along with socio-cultural characteristics. Nepal, however, is known economically poor but richer in natural resources like herbal plants. Before emerging of advanced technology of medical science in Nepal, almost Nepalese people were under treatment with medicinal plants. Such domestic treatment is continued since an immense time and still in rural areas but in recent days, practice of herbal use and treatment are going to be displaced, and medicinal plants are in high risk of vanishing due to increasing urbanization, human residence, over harvesting, deforestation etc. Bankariyas are found socially, economically, and academically very poor and back ward as people of Stone Age and still believed in shamanism, god and ghost. If someone becomes sick, they do not take patient to hospital without consultation their traditional healer or shaman’s incantation. Shamans are consulate to find the sickness that what happened with sick. Because, healer keeps knowledge that what happened with sick, what kind of treatment is necessary and what herbs work for what disease and incident. According to situation shaman starts treatment either incanting with esoteric words praying deity/god or herbal treatment. Therefore, they found having sound knowledge of traditional healing. At present, such amazing treatment practice has been going to be vanishing. Hence, to keep it alive this study was conducted based on census survey to obtain socioeconomic data as quantitative and healers were consulted as homeopathic doctor as qualitative research design.